The Mathematical Literacy Ability of Level 3 Students in Solving PISA-liked Problems at Mathematics-Class Program of MAN 1 Jember - Dimas Danar Septiadi (Universitas Teknokrat Indonesia, 2022)
This study aims to describe students’ mathematical literacy ability of grade 10 in solving PISA-liked Problems. The students' abilities were seen from 7 mathematical literacy competencies in the solving PISA problems. The research subjects were 3 students of grade 10 of the EKA Mathematic Program, Class A, in MAN 1 Jember at level 3. The method in collecting data was tests, interviews, and documentation. The data analysis used Miles and Huberman data analysis which consists of data collection, data condensation, data display and conclusion. The data is validated using subject triangulation. The results of this study indicated that students at level 3 show good criteria in the communication aspect; mathematization; representation; reasoning and argument; and they were able to choose strategies in solving PISA-liked problems. There are some skills that did not use in solving mathematical literacy, in this case, which is using correct symbols and mathematical tools. Even though level 3 students failed in this skills and failed in use a correct unit, mentally, they success to find the correct solution. Students with mathematical literacy skills at level 3 were categorized as intermediate students who can solve moderate and low level of problems; however, they still had difficulties in solving very high-level problems.Keywords: mathematical literacy, problem solving, PISA-liked problems